Red Beet Process Waste: A Sustainable Glucose Syrup Alternative for Gummy Confectionery - Elobeid, Tahra; Tuzun, Burcu; Apaydin, Ayse; Tekneci, Ezgi; Palabiyik, Ibrahim; Toker, Omer Said; Konar, Nevzat; Atalar, Ilyas (WILEY, 2025)
Red beet (RB) is a key component in the natural colorant market. Various efficiency challenges, arising from process waste, affect their production. Disposal of these wastes elevates production costs and poses environmental risks. Innovative approaches have been explored to repurpose process waste to align with the circular economy. A rising trend in food technology is substituting corn syrup with clarified fruit juices or concentrates. This study aims to develop an alternative to glucose syrup from fluid waste (red beet liquid waste; RBLW) (similar to 12.0 degrees Bx), which is released after pigment extraction from RB (Beta vulgaris L.), and to determine its potential application in gummy formulations. This study examined the clarification and decolorization of samples using ion exchange and adsorbent resins at varying flow rates, followed by evaporation. Composition and visual properties were analyzed. Under optimal conditions, the clarified and decolorized residue (clarified and decolorized red beet liquid waste [CD-RBLW]) showed a high T625 value (77.3%) and was incorporated in gummy formulations. A Custom Mixture Design (n = 14) tested CD-RBLW, glucose syrup, and gelatin as independent variables. In addition, gummy samples were stored under accelerated shelf-life conditions (25 degrees C/70% relative humidity [RH]) for 8 weeks, and changes in hardness, color difference (Delta E), moisture content, and water activity values were monitored. After processing, RBLW demonstrated functionality comparable to glucose syrup in gummy formulations.
Keywords: colorings; confectionery; corn syrup; red beet; waste treatment; BETA-VULGARIS-L.; ISOMALTULOSE; DEGRADATION; STABILITY; MOISTURE; Food Science & Technology